2011
DOI: 10.1007/s12032-011-9967-z
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate antigen 242 highly consists with carbohydrate antigen 19-9 in diagnosis and prognosis of colorectal cancer: study on 185 cases

Abstract: The objective of the study was to compare the clinical value of preoperative serum carbohydrate antigen 19-9 (CA19-9) and carbohydrate antigen 242 (CA242) in diagnosis and prognosis for 5-year recurrence-free survival (RFS) in patients with colorectal cancer (CRC). Preoperative serum CA19-9 and CA242 concentrations were detected by C12 protein chip diagnostic system in 185 patients with CRC, and informative data were collected during 5-year follow-up periods. The value of CA19-9 and CA242 in diagnosis and prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…Some studies have reported that CA 242 has superior value in pancreatic carcinoma and colorectal carcinoma (Carpelan-Holmstrom et al, 1996;Ni et al, 2005;Yang et al, 2012), but few have examined the relationship between these two tumor markers and gastric cancer. Our study analyzed the levels of expression of CA 242 and CA 50 in gastric cancer patients, finding that serum CA 242 and CA 50 levels had a significant positive correlation with the lymph node status and tumor stage.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported that CA 242 has superior value in pancreatic carcinoma and colorectal carcinoma (Carpelan-Holmstrom et al, 1996;Ni et al, 2005;Yang et al, 2012), but few have examined the relationship between these two tumor markers and gastric cancer. Our study analyzed the levels of expression of CA 242 and CA 50 in gastric cancer patients, finding that serum CA 242 and CA 50 levels had a significant positive correlation with the lymph node status and tumor stage.…”
Section: Discussionmentioning
confidence: 99%
“…Pancreatic cancer has been the leading clinical application for CA242 because of its excellent performance in this cancer. Some small-scale studies have investigated CA242 in gallbladder carcinoma and cholangiocarcinoma [7,14,25,28], but due to the sample size or quality of these studies, the credible AUC values for these two carcinomas are still unknown. Therefore, our ndings indicate that CA242 is also suitable for use as a biomarker for cholangiocarcinoma and gallbladder cancer, whose AUCs were 0.8145 (0.7737, 0.8553) and 0.8349 (0.8157, 0.8542), respectively ( Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…We found that CA242 levels were elevated in a variety of digestive system cancers, including pancreatic cancer, gallbladder cancer, cholangiocarcinoma, colorectal cancer, and gastric cancer, which was consistent with previous reports. The AUC values of the ROC curves for pancreatic cancer, gallbladder carcinoma, and cholangiocarcinoma were all greater than 0.8, but only pancreatic cancer has been studied in detail [4,10,13,17,22,[25][26][27]. Previous studies have shown that CA242 alone or in combination with other biomarkers can predict the diagnosis, progression, and prognosis of pancreatic cancer [4, 7, 10, 12-16, 23, 24].…”
Section: Discussionmentioning
confidence: 99%